On-Board Equipment and Application Areas of Unmanned Aerial Vehicles - Mammadov, A.Z. (Herald of Azerbaijan Engineering Academy, 2024)
Initially used only for military and surveillance purposes, unmanned aerial vehicles (UAVs) have been used in engineering, scientific research, and civil fields in recent years due to the reduction in costs and increased availability with advancing technology. UAVs use various active or passive sensors to obtain the necessary information from these areas with high accuracy. UAVs with these capabilities can provide more accurate, sensitive, fast information and analytical solutions than manned aircraft or satellite images. In the presented article, the structural structure of UAVs was analyzed and the classification forms were determined. The sensors on board UAVs are examined, and their future development prospects are shown. In addition, the on-board equipment, mechanical components, types of payloads of UAVs were examined by showing specific examples and their characteristics were determined.